Identities Relating the Angular and Coordinate Components of Axial Aberration in the Fringing Field of the Magnetic Sector of Static Mass Analyzer - Sachenko, V. D.; Antonov, A. S. (Journal of analytical chemistry (New York, N.Y.), 2022)
We derived identities that relate the angular and coordinate elements of the 2nd order transfer matrix, which determine the axial aberration of static mass analyzers in the fringing field of the magnetic sector with an arbitrary entrance of ions. These identities can be used as criteria for the correct calculation of the axial aberration of the mass analyzer and its resolution.